(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article is devoted to functioning of hortatory modality in a modern publicity environment. A question about the structural and psycholinguistic features of hortatory constructions is examined.